Beyond passive consumption: Dis/ordering water supply and sanitation at Hanoi's urban edge. Issue 85 (October 2017) - Schramm, Sophie; Wright-Contreras, Lucía
Highlights: Dynamics of service provision differ between water and sanitation at Hanoi's edge. Finance and real estate shape an uneven expansion of central and decentral networks. People engage with the emerging multiplicity of differently networked spaces. This engagement expresses agency as much as a precarious lack of alternatives. People create not only situational linkages but also rather stable collectives. Abstract: In Hanoi people access, expand and create water and sanitation infrastructures in multiple ways that include, but are not restricted to, external provision of networked services. Urban master planning and the construction of large technological networks aim at integrating the urban region based on circulating 'modern ideals' of ubiquity and standardization of infrastructures. However, centralized infrastructure provision has remained unstable and spatially uneven. We examine differently networked spaces that have emerged at the edge of Hanoi along with rapid urban change and new financing mechanisms in the past thirty years, and the ways in which urban residents engage with the various water and sanitation systems. This engagement is shaped by circulating ideals, place-specific processes of urban re-production, sector-specific dynamics, and individuals. Not only in periurban villages, but also in modern housing estates, people rebut a role as passive receptors of external services. In some instances, they create relatively stable collectives through which they provide, negotiate and complement networked infrastructure connection. Thus, people living at Hanoi's urban edge actively re-produce water and sanitation systems beyond passive consumption of externally provided services.